Management of a crown-root fracture in central incisors with 180° rotation: A case report - Sahebi, Safoora; Dolatkhah, Vahid; Shojaee, Nooshin Sadat (Iranian Endodontic Journal, 2011)
<span style="font-style: normal; font-family: "Cambria","serif"; color: black; font-size: 10pt; mso-bidi-language: FA; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: ZH-CN; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US;"> ABSTRACT: The crown-root fracture is a common tooth injury which compromises the biological width and need proper endodontic and prosthodontic treatment to achieve acceptable clinical outcome. This case report describes clinical management of crown-root fracture in maxillary central incisors which was successfully treated by forceps eruption with 180˚ rotation to restore the biological width. The patient was followed-up for 18 months. Clinical and radiographic evaluation showed acceptable results, the replanted teeth have normal function and no obvious inflammatory root resorption was seen on radiographic examination.